2021
DOI: 10.1039/d0em00394h
|View full text |Cite
|
Sign up to set email alerts
|

Interactions with freshwater biofilms cause rapid removal of common herbicides through degradation – evidence from microcosm studies

Abstract: We found that biofilms drive the removal of bentazone, metazachlor and metribuzin from water through rapid mineralization of these herbicides, rather than by their sorption and accumulation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 37 publications
(38 reference statements)
0
4
0
Order By: Relevance
“…The thermometer symbol indicates an effect related to temperature only, whereas the symbols of the thermometer and of the chemical together indicate a combined effect of both. (1) Bighiu & Goedkoop ( 2021 ), (2) Zeng et al ( 2014 ), (3) Zamarreňo et al ( 2009 ), (4) Höfle ( 1979 ), (5) White et al ( 1991 ), (6) Berthelot et al ( 2019 ), (7) Hayes et al ( 2019 ), (8) Klausmeier et al ( 2004 ), (9) Duarte et al ( 2013 ), (10) Donnelly et al ( 1990 ), (11) Stelzer et al ( 2003 ), (12) Fernandes et al ( 2012 ), (13) Phillips et al ( 2017 ), (14) Kaushik and Hynes ( 1971 ), (15) Pomeroy and Wiebe ( 1988 ), (16) Delnat et al ( 2021 ), (17) Wickham et al ( 2020 ), and (18) Arias Font et al ( 2021 )…”
Section: Resultsmentioning
confidence: 99%
“…The thermometer symbol indicates an effect related to temperature only, whereas the symbols of the thermometer and of the chemical together indicate a combined effect of both. (1) Bighiu & Goedkoop ( 2021 ), (2) Zeng et al ( 2014 ), (3) Zamarreňo et al ( 2009 ), (4) Höfle ( 1979 ), (5) White et al ( 1991 ), (6) Berthelot et al ( 2019 ), (7) Hayes et al ( 2019 ), (8) Klausmeier et al ( 2004 ), (9) Duarte et al ( 2013 ), (10) Donnelly et al ( 1990 ), (11) Stelzer et al ( 2003 ), (12) Fernandes et al ( 2012 ), (13) Phillips et al ( 2017 ), (14) Kaushik and Hynes ( 1971 ), (15) Pomeroy and Wiebe ( 1988 ), (16) Delnat et al ( 2021 ), (17) Wickham et al ( 2020 ), and (18) Arias Font et al ( 2021 )…”
Section: Resultsmentioning
confidence: 99%
“…The PFAS attenuation between sites DS1 and DS2 was not likely due to dilution from additional surface water or groundwater input as streamflow was observed to be decreasing through this stream section (Table S3) and has been documented to be a losing reach during base-flow conditions. , Thus, this decrease in PFAS concentration between DS1 and DS2 was likely due to other potential attenuation processes such as sorption to sediment and biodegradation via biofilms. Previous research has documented that biofilms can rapidly degrade organic contaminants in surface waters …”
Section: Resultsmentioning
confidence: 99%
“…Previous research has documented that biofilms can rapidly degrade organic contaminants in surface waters. 64 Temporal Distribution. Seven of 10 basins with available flow information and corresponding PFAS detections in at least one of the temporal samples collected (Table S3) provided preliminary evidence of an inverse relation between PFAS and streamflow, with six of these sites having PFAS detected only in the sample where the lowest flow was observed (Table S3).…”
Section: ■ Materials and Methodsmentioning
confidence: 99%
“…They flourish in nutrientrich wastewater in various morphological features, such as unicellular, filamentous, or colonial forms, forming a mat-like structure [38][39][40][41][42]. Despite being an efficient global sink for atmospheric carbon through the photosynthetic process and natural nitrogen fixation they are also utilized as bio-agents for aquatic pollutant removal [43][44][45][46]. Recently, it has been reported that cyanobacterial growth significantly ameliorates the negative effects of herbicides and pesticides [47] in aquatic and terrestrial ecosystems.…”
Section: Introductionmentioning
confidence: 99%